1991
DOI: 10.1159/000213277
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Elevation of Lipid Peroxidation Products: Diminution of Superoxide Dismutase Activity in the Central Nervous System of Rats

Abstract: Alteration in lipid peroxidation products such as lipid peroxides, lipid hydroperoxides were studied in different regions of CNS of ageing rats (13, 26, 52, 78 and 104 weeks). The levels of lipid peroxide and lipid hydroperoxide were increased in various regions of brain and spinal cord. However, the activity of superoxide dismutase was decreased in cerebrum, hypothalamus, hippocampus, cerebellum, brain stem and spinal cord. The present communication demonstrates that the different parts of CNS at 13 and 26 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…A growing body of evidence suggests that reactive ROS play a crucial role in the development of these impairments as discussed above (Yamada et al 1995;Kucukatay et al 2007). The increased production of oxidants altered neurotransmitter release and increased membrane permeability (Gupta et al 1991). Besides, free radicals may degrade nitric oxide (NO), which plays an important role as a diffusible intercellular signaling molecule (a neurotransmitter in the central nervous system) (Geyer et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that reactive ROS play a crucial role in the development of these impairments as discussed above (Yamada et al 1995;Kucukatay et al 2007). The increased production of oxidants altered neurotransmitter release and increased membrane permeability (Gupta et al 1991). Besides, free radicals may degrade nitric oxide (NO), which plays an important role as a diffusible intercellular signaling molecule (a neurotransmitter in the central nervous system) (Geyer et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that oxidative stress may in part contribute to the pathogenesis of PH in a MCT model [33,34] . The antioxidative defense is largely provided by several enzymes such as SOD, GSH-Px, and CAT [35][36][37] . Meng and coworkers [25] indicated that low doses of SO 2 (22 and 56 mg/m 3 ) caused significant increases in SOD, GSH-Px, and CAT activities in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of lipidperoxidation products are also increased with aging (44,83,87,97,108,113,119,123). In addition, aging-related oxidative modification of different proteins causes changes in protein structure, enzyme activities, transcriptional activities, and signal-transduction pathways (32,70,103,111,112,124), leading to age-related diseases.…”
Section: Liu and Xumentioning
confidence: 99%